Expression of PD-L1 on Monocytes Is a Novel Predictor of Prognosis in Natural Killer/T-Cell Lymphoma - Zhang, Xue-wen; Bi, Xi-wen; Liu, Pan-pan; Liu, Ze-long; Nie, Man; Yang, Hang; Lei, De-xin; Xia, Yi; Jiang, Wen-qi; Zeng, Wei-an (Frontiers in Oncology, 2020)
Background: Natural killer/T-cell lymphoma (NKTCL) is a highly aggressive lymphoma with a dismal prognosis, and novel therapeutic targets are urgently needed. Programmed death-ligand 1 (PD-L1) has become a promising therapeutic target for various cancers, but most of the studies have focused on expression of PD-L1 on tumor cells. Expression of PD-L1 on tumor-infiltrating nonmalignant cells, especially monocytes, has not been studied in NKTCL, and its prognostic value remains unknown. Materials and methods: Expression of PD-L1 on tumor-infiltrating stromal cells was measured in NKTert and HS5 cells when cultured alone or co-cultured with NKTCL cell lines. Clinical samples were collected from 42 patients with newly diagnosed NKTCL. Expression of PD-L1 on monocytes was analyzed in patients’ peripheral blood and tumor tissues using flow cytometry and immunofluorescent staining, respectively. Survival data were retrospectively collected and the prognostic significance of PD-L1 expression on monocytes was analyzed. Results: PD-L1 expression on tumor-infiltrating stromal cells was remarkably elevated when co-cultured with NKTCL cells. The percentage of PD-L1+ monocytes among all monocytes in peripheral blood was significantly higher in NKTCL patients than that in healthy individuals. Among NKTCL patients, percentage of PD-L1+ monocytes in blood positively correlated with that in tumor tissues. Patients with a higher percentage (≥78.2%) of PD-L1+ monocytes in blood or with a higher percentage (≥24.2%) of PD-L1+ monocytes in tumor tissues exhibited a significantly inferior survival, compared with their counterparts. A higher percentage of PD-L1+ monocytes in blood or tumor tissues was an independent adverse prognostic factor. Conclusions: Expression of PD-L1 on monocytes is up-regulated and has significant prognostic value in patients with NKTCL.